Simplified model and performance analysis for radiant cooling panel with serpentine tube arrangement and thin insulation layer for moisture control in tropical climate - Ahmad N.A.; Lim C.W. (IOP Publishing Ltd, 2023)
Computer software; Condensation; Energy conservation; Flow of fluids; Heat resistance; Insulation; Moisture control; Numerical models; Silicate minerals; Tropics; Cooling Capacity; Insulation layers; Moisture condensation; Performance analysis; Principle of superposition; Serpentine tubes; Simulation software; Tropical climates; Climate models